Prediksi Penjualan Tempered Glass Handphone Xiaomi Menggunakan Metode Least Square - Fahriansyah Patompo; Irvan Abraham Salihi (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
ABSTRACT The Amanda Cell store is a Xiaomi handphone tempered glass sales store. So far, the Amanda Cell Store has not been able to predict the ups and downs of Xiaomi cell phone tempered glass sales. This problem affects the ordering process for goods while in fact, some have to wait for sold-out sales. It is a result of the emptiness of tempered glass on other cellphone brands and the cumulation of unsold tempered glass causing some losses. To overcome the problems, an application that can perform a prediction to find out the types of Tempered Glass Xiaomi Mobile is required. The purpose of this study is to find out the results of applying the Least Square Method to predict sales of Tempered Glass for Xiaomi Mobile Phones and to know the level of accuracy of Xiaomi's Tempered Glass sales prediction using the Least Square method. This study results in a conclusion that June 2022 's Prediction is 27,037 and July 2022's prediction is 7,087 Keywords: Sales Prediction, Least Square